Writing development in struggling learners : understanding the needs of writers across the lifecourse - Miller, Brett; McCardle, Peggy; Connelly, Vince (Studies in writing ;, 2018)
"In 'Writing Development in Struggling Learners', international writing researchers provide critical insights into the development of writing skills for individuals who struggle to become proficient writers. This edited volume takes a life course view and examines concepts for development of writing skills with a focus on where learners struggle, why this may occur for those without and without specific learning disorders (SLDs), how to identify these learners and what we can do to facilitate efficient writing. Throughout the volume, struggling learners are presented with a holistic lens; contributors succinctly synthesize the literature base and present insights into the current state of the science and areas of future need and advancement."--Provided by publisher